Considering life and death: a qualitative vignette study among farm animal veterinarians in the Netherlands on considerations in end-of-life decision-making - Deelen, Ellen; Meijboom, Franck L. B.; Tobias, Tijs J.; Koster, Ferry; Hesselink, Jan Willem; Rodenburg, T. Bas (Frontiers in Animal Science, 2023)
Farm animal veterinarians are frequently involved in animals’ end-of-life (EoL) situations. Existing literature found that the decision-making process to end an animal’s life can be experienced as complex and stressful by veterinarians. The complexity of the process may find its origin in the multiple medical and non-medical aspects that veterinarians consider coming to their decision. Although research provides insight into what considerations are at stake, the literature does not provide information on how these aspects affect the decision-making process. This study explores how different considerations affect the decision-making process of farm animal veterinarians in EoL situations. Semi-structured interviews were conducted with nineteen farm animal veterinarians in the Netherlands. During the interviews, case scenarios in the form of vignettes were used to identify and explore the considerations that play a role for these veterinarians in EoL decision-making. Based on the analysis of the interview data, we discovered that farm animal veterinarians consider EoL situations using one of three identified frames: function, prospect, and duty. These frames illustrate one’s perspective on the interplay of medical and non-medical aspects. As such, the key contributions of this study are the discovery of the importance of the interplay between considerations in EoL decision-making and the frame-specific approach of veterinarians. The identified frames may relate to the coping strategies of veterinarians dealing with the complexity of EoL situations.